Solution-phase synthesis of un-doped and Pb doped CdO films - (:unkn) unknown (ACADEMIC PRESS LTD- ELSEVIER SCIENCE LTD, 2014)
In this work, un-doped and Pb doped cadmium oxide (CdO) films were prepared for the first time on glass substrates by successive ionic layer adsorption and reaction (SILAR) technique. The crystal structure parameters such as average crystallite size and dislocation density were calculated from X-ray diffraction analysis. XRD analysis showed that the films have poly-crystalline structures with decent crystallinity levels. Surface morphology was found to be modified with various Pb doping concentrations. The diameters of the nanoparticles were calculated from the SEM. The optical properties of the prepared CdO films were characterized by ultraviolet-visible spectrophotometer. With the increase in Pb concantration from 0.5% to 2.5%, the optical absorption edge shifted towards shorter wavelengths which might be attributed to change in crystallite size. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Pb-doping; SILAR; CdO; Optical properties; CUO THIN-FILMS; OPTICAL-PROPERTIES; HEAT-TREATMENT; FABRICATION; DEPOSITION; ZNO